2020
DOI: 10.1093/cid/ciaa1443
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind, Randomized, Placebo-controlled Trial With N-acetylcysteine for Treatment of Severe Acute Respiratory Syndrome Caused by Coronavirus Disease 2019 (COVID-19)

Abstract: Background A local increase in angiotensin 2 after inactivation of angiotensin-converting enzyme 2 by SARS-CoV-2 may induce a redox imbalance in alveolar epithelium cells, causing apoptosis, increased inflammation and, consequently, impaired gas exchange. We hypothesized that N-acetylcysteine (NAC) administration could restore this redox homeostasis and suppress unfavorable evolution in Covid-19 patients. Objective To determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 33 publications
6
87
2
2
Order By: Relevance
“…The effect of NAC in COVID-19 in a double-blind, randomized, placebocontrolled and unicentric trial, conducted in 135 patients with the severe disease (confirmed or suspected), having as a primary endpoint the need for mechanical ventilation was recently published. Time of mechanical ventilation, admission to ICU, time in ICU, and mortality were secondary endpoints of this paper and it was found that administration of NAC in high doses did not affect the evolution of severe form of COVID-19 [69]. The difference with our study resides in the studied populations, the doses of NAC and in the fact that the authors did not explain whether the therapy was an adjuvant to standard comprehensive management.…”
Section: Discussionmentioning
confidence: 53%
“…The effect of NAC in COVID-19 in a double-blind, randomized, placebocontrolled and unicentric trial, conducted in 135 patients with the severe disease (confirmed or suspected), having as a primary endpoint the need for mechanical ventilation was recently published. Time of mechanical ventilation, admission to ICU, time in ICU, and mortality were secondary endpoints of this paper and it was found that administration of NAC in high doses did not affect the evolution of severe form of COVID-19 [69]. The difference with our study resides in the studied populations, the doses of NAC and in the fact that the authors did not explain whether the therapy was an adjuvant to standard comprehensive management.…”
Section: Discussionmentioning
confidence: 53%
“…Current usage of NAC in a clinical setting against the coronavirus infection shows controversial results. While in some clinical cases a positive outcome was reported (Ibrahim et al, 2020;Alamdari et al, 2020), a recent double-blinded clinical study conducted in Brazil did not find a significant difference between placebo and experimental groups (de Alencar et al, 2020). More evidence for the effectiveness of NAC in SARS-CoV-2 treatment should be obtained from newly established clinical trials: "Efficacy of N-Acetylcysteine (NAC) in Preventing COVID-19 from Progressing to Severe Disease," identifier NCT04419025 and "A Study of N-acetylcysteine in Patients with COVID-19 Infection," NCT04374461 (clinicaltrials.gov).…”
Section: Discussionmentioning
confidence: 95%
“…In another small trial (n=20), administration of enoxaparin significantly reduced the median number of ventilator-free days compared with low molecular weight/ unfractionated heparin (0 versus 15 days; p=0.028) and resulted in a higher ratio of successful liberation from mechanical ventilation after respiratory failure (HR 4.0 (95% CI 1.035-15.053); p=0.031) in patients with severe COVID-19 (supplementary table 4) [54]. Trials of ruxolitinib, N-acetylcysteine and rhG-CSF (n=43-200) showed no significant efficacy in reducing need for ventilation in patients with severe COVID-19 [32,48,49] ( figure 4b and supplementary table 4).…”
Section: Antimalarial and Mucolytic Drugsmentioning
confidence: 99%
“…Other therapies Trials (n=20-135) investigating the kinase inhibitor, ruxolitinib [32], the calcium release-activated calcium channel inhibitor, auxora [56], the anticoagulant, enoxaparin [54], and N-acetylcysteine, a mucolytic drug with anti-oxidant properties [49], in patients with severe COVID-19 reported no significant difference in mortality versus the comparator groups (figure 2c). One trial (n=200) reported a reduced 21-day mortality with recombinant human granulocyte colony-stimulating factor (rhG-CSF) added to standard care versus standard care alone (HR 0.19 (95% CI 0.04-0.88)) in patients with severe COVID-19 [48].…”
Section: Antimalarial and Mucolytic Drugsmentioning
confidence: 99%
See 1 more Smart Citation